(untitled) (Sciences & Technology. A, exactes sciences, 2007)
In opposite of classical holography, the opto-digital holography recording step is based on CCD (charge coupled device) sensors and the optical reconstruction step is based on LCD (liquid crystal displays) or DMD (digital mirror displays) devices. Knowing, that the important disadvantage of these elements was their pixel size which was relatively high comparatively to the classical photoplate’s grains size, it was not possible to make holograms of large objects. The quick evolution of these imaging devices, these last few years, permits to find, such devices with relatively low pixel size (nearly 4 μm for CCD and 7 μm for LCD). It is then possible to work on voluminous objects and to get best holograms quality. We show in this work that it is possible to record and reconstruct holograms of objects having several cms square. Since all the process is controlled numerically, it is possible to follow in real time using the holographic interferometry techniques, double exposure, real time or time average, any changes in the object under study and to start and stop the process at any time by adequate software. This can be done by subtracting a reference image by suitable software directly on the CCD camera. We show also, the ability of the technique to study in real time all evolutional phenomena.